Electrical Properties of Lumbar Paraspinal Muscles in Young Adults With and Without Chronic Low Back Pain Based on Electrical Impedance Myography: A Cross-Sectional Study - Wang, Hongjiang; Zheng, Jiaxuan; Yu, Qiuhua; Fan, Ziyan; Lo, Wai Leung Ambrose; Li, Le; Wang, Chuhuai (Frontiers in Neurology, 2022)
Background: Lumbar paraspinal muscle (LPM) is important in spinal stabilization in patients with chronic low back pain (CLBP). However, the electrical properties of LPM in patients with CLBP remains unclear. Electrical impedance myography (EIM) is a novel and non-invasive technique that provides a simple quantitative evaluation of electrical properties of the LPM. Purpose: This study aimed to apply EIM to assess the electrical properties of the LPM between patients with CLBP and healthy control (HC). Methods: Thirty participants (15 CLBP participants; 15 healthy controls) were enrolled in the study. Participants in the CLBP group were asked to complete the Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), and Roland–Morris Disability Questionnaire (RDQ) to assess the pain intensity and disability in daily life. Independent sample t-tests were adopted to analyze the basic characteristics between the two groups. At 5 kHz, 50 kHz, 100 kHz, and 200 kHz current frequencies, the electrical properties were measured on each side of the LPM. The EIM parameters of resistance (R), reactance (X), phase angle (PA), and Z value were analyzed by one-way analysis of variance, with age as covariate. Spearman’s rank correlation coefficient analysis was applied to explore the relationships between the questionnaires and the EIM parameters. Results: The R and Z values of bilateral LPM in the CLBP group were significantly larger than those in the HC group; the PA decreased and the X did not change at these four tested current frequencies. At 5 kHz, Z and R on the right side were non-significantly different between patients and HCs. Correlation analysis showed that at 50 kHz, ODI and RDQ scores correlated negatively with the R of the bilateral LPM (r=0.523, r=0.581, respectively; P<0.05). RDQ scores correlated positively with the PA of the right LPM (r=0.521, P<0.05). Conclusion: The electrical properties of the bilateral LPM differed between CLBP participants and healthy individuals, regardless of the different frequencies used. These altered electrical properties of the LPM in the patients with CLBP correlated to some extent with disability in daily life.